(untitled) (The Review of Diabetic Studies, 2024)
Background: Interprofessional training (IPT) has become a central strategy for improving collaborative practice and enhancing measurable healthcare quality indicators. As modern healthcare systems increasingly rely on multidisciplinary teams—including physicians, nurses, dentists, allied health technicians, and administrators—effective team-based training is essential for strengthening patient safety, communication, workflow efficiency, and overall care quality. Objective: This systematic review aimed to evaluate the effectiveness of interprofessional training programs implemented between 2020 and 2024 in improving healthcare quality indicators across diverse healthcare professions. The review assessed the types of IPT interventions, participating professional groups, measured quality indicators, and the extent to which IPT contributed to measurable improvements in healthcare outcomes. Methods: Following PRISMA 2020 guidelines, six major databases (PubMed, Scopus, Web of Science, CINAHL, Google Scholar, and Saudi Digital Library) were systematically searched for studies published between January 2020 and December 2024. Empirical studies evaluating structured IPT programs for healthcare professionals were included. Fourteen studies met the inclusion criteria. Data extraction focused on training modalities, participant professions, outcome measures, and key findings. Risk of bias was assessed using JBI, CASP, and RoB tools according to study design. Results: Interprofessional training demonstrated consistent positive effects across five major domains of healthcare quality. The strongest improvements were observed in patient safety outcomes, including enhanced safety culture, increased adherence to safety protocols, and improved crisis-response coordination. Medication safety also improved, with reductions in discrepancies and near-miss events among pharmacy technicians, nurses, and physicians. All included studies showed advancements in interprofessional communication, role clarity, and teamwork climate. Workflow efficiency improved through reduced waiting times, better task distribution, and enhanced departmental coordination. Studies measuring patient satisfaction reported higher scores related to communication clarity, efficiency, and perceived collaboration among staff. Simulation-based IPT yielded the most immediate performance gains. However, long-term patient-outcome data and standardized quality indicators remain limited. Conclusion: Interprofessional training programs implemented between 2020 and 2024 were effective in improving multiple healthcare quality indicators, particularly patient safety, communication, and workflow efficiency. These findings underscore the importance of integrating structured IPT across healthcare professions—including allied health and administrative staff—to enhance collaboration and organizational performance. Future research should employ more rigorous study designs, standardized outcome measures, and longer follow-up periods to better understand the sustained impact of IPT on clinical outcomes.